PENINGKATAN MINAT KETERAMPILAN MEMBACA MELALUI MEDIA POWER POINT INTERAKTIF PESERTA DIDIK KELAS II MIN 3 LUWU KECAMATAN SULI KABUPATEN LUWU TAHUN PELAJARAN 2022/2023 - Ramlah (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
The research is motivaled by the hope that the implementation of the teaching and learning process for Indonesian subjects, especially in increasing interest in reading skills through Interactive Power Point media can be carried out completely in accordance with the specified Minimum Comleteness Criteria (KKM). The purpose of this study is to obtain an objective picture of improving Indonesian language learning outcomes. Reading skills throughInteractive Power Point media in class II  second semester students of MIN 3 Luwu Suli District, Luwu Regency. The purpose og this Classroom Action research is to increace interest in reading skills through Interactive Power Point media in class II semester I students at MIN 3 Luwu Suli District, Luwu Regency. From the data analysis, it was found that students’learning motivation increased  from the pre-cycle. Student achievement also increased  from pre –cycle, cycle I to cycle II gradually. The conslution of this study reveals that the use of interactive power point media can improve the process of learning to read. This is indicated by an increase in student activity in responding to the teacher when asking qestions about the content of the story, which 50 % and an increase in concluding the content of the story he reads, which is 41,67%. Furthermore, this causes the studets’ reading aloud ability to increase. The increase in the ability to read aloud through interative PPT media in first cycle was 5,06, the initial condition of 63 increased to 68,06. In the second cycle it increased by 12,59, the initial condition of 63 increased to 75,59. Keywords: Learning Outcomes,reading skills, interactive power point media.